INFLUENCE MINERAL FERTILIZERS AND BIOLOGICALS ON GRAIN QUALITY OF WHEAT HARD FURIOUS - Шевніков, Д. М. (Scientific Progress & Innovations, 2013)
Application of mineral fertilizers and inoculation of seed of wheat hard furious by biologics influenced positively the physical indexes of quality. The nature of wheat grain was more on areas with inoculated seeds by diazofit and polimiksobakteryn on the background of a fertilizer “straw + N10 on the ton of side products” (789 g/l); for the use ща these two preparations separately, there was got, accordingly – 788 and 792 g/l, control (without fertilizers and inoculation) – 762 g/l. By introduction of mineral fertilizers N45Р45К30 the nature of grain without inoculation was 781 g/l, and by its application by polimiksobakteryn – 783, diazofit – 786, by compatible use of these two preparations – 786 g/l.